Role of Preoperative CEA, CA 19-9, NLR and PLR as Predictors of Adverse Prognostic Pathological Features of Gastric Carcinoma Patients in a Tertiary Centre of Nepal - Mandal, Rajesh K; Bhandari, Ramesh S; Joshi Lakhey, Paleswan; Singh, Yogendra P; Vaidya, Pradeep; Kansakar, Prasan BS; Ghimire, Bikal; Kandel, Bishnu P (Journal of Institute of Medicine Nepal, 2019)
Introduction According to GLOBOCAN 2018, gastric carcinoma is the fifth most common cancer (5.7%) and third most common cause of cancer related death (8.2%) worldwide. Delayed presentation and advanced disease at diagnosis, owing to the overlapping symptoms, can be attributed to its high mortality. Gastrectomy is one of the most commonly performed surgery at our centre. This study aims to study the role of pre-operative serum carcinoembryonic antigen (CEA), carbohydrate antigen 19-9 (CA 19-9), neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR) as predictors of adverse prognostic pathological features of gastric carcinoma patients who were considered for surgery at our centre. Methods This is a retrospective analysis of prospectively maintained database of all operated gastric carcinoma patients since June 2016 to January 2019. Various pre-operative variables including serum CEA level, serum CA 19-9 level, NLR and PLR were collected. Intra-operative surgical procedures performed and post-operative pathologic variables like tumor size, stage, grade, lymph node ratio (LNR), lymphovascular invasion (LVI) and perineural invasion (PNI) were collected. Results A total 60 patients were planned for surgical intervention over this duration. Mean age of the population was 56.8±12.5 years with slight male predominance (i.e. 55%). Mean CEA level was 6.17 ng/ml and CA 19-9 level was 72.1 U/ml. The mean NLR and PLR of the study population was 3.4 and 200 respectively. Fifty four patients had distal tumors and six had proximal tumors. Curative surgery was performed in 40 patients out of which 37 underwent subtotal gastrectomy and three underwent total gastrectomy. D2 gastrectomy was performed in 55% patients treated with curative intention. Advanced disease (T2 and above) was seen in 86.7% of patients. Preoperative CEA, CA 19-9, NLR, PLR were evaluated for association with pathologic features like tumor size, T stage, grade of tumor, LNR, LVI, and PNI but statistical analysis failed to show any significant association. Conclusion Advanced disease at presentation is common in gastric carcinoma. Preoperative clinical parameters including tumor markers CEA, CA 19-9, NLR and PLR may not be useful to diagnose the advanced disease in gastric carcinoma patients.